The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.watres.2014.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of copper nanoparticles into paper for point-of-use water purification

Abstract: As a cost-effective alternative to silver nanoparticles, we have investigated the use of copper nanoparticles in paper filters for point-of-use water purification. This work reports an environmentally benign method for the direct in situ preparation of copper nanoparticles (CuNPs) in paper by reducing sorbed copper ions with ascorbic acid. Copper nanoparticles were quickly formed in less than 10 minutes and were well distributed on the paper fiber surfaces. Paper sheets were characterized by x-ray diffraction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(82 citation statements)
references
References 24 publications
1
79
0
Order By: Relevance
“…Based on the antifungal and antimicrobial properties of Cu + 2 , Cu NPs are actively being developed for applications in agriculture and food preservation (Park et al, 2015;Montes et al, 2015;Dugal and Mascarenhas, 2015;Ray et al, 2015;Kalatehjari et al, 2015;Ponmurugan et al, 2016;Maniprasad et al, 2015;Majumder and Neogi, 2016;Villanueva et al, 2016), textiles (Majumder and Neogi, 2016;Sedighi and Montazer, 2016), paints, coatings (e.g. lumber treatment) and water treatment (Ben-Sasson et al, 2016;Ma et al, 2016;Dankovich and Smith, 2014). The number of applications for regulatory approval of Cu-based nanopesticides has increased substantially in the past few years, highlighting the need for information about the likely exposure routes, doses and adverse effects on non-target organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the antifungal and antimicrobial properties of Cu + 2 , Cu NPs are actively being developed for applications in agriculture and food preservation (Park et al, 2015;Montes et al, 2015;Dugal and Mascarenhas, 2015;Ray et al, 2015;Kalatehjari et al, 2015;Ponmurugan et al, 2016;Maniprasad et al, 2015;Majumder and Neogi, 2016;Villanueva et al, 2016), textiles (Majumder and Neogi, 2016;Sedighi and Montazer, 2016), paints, coatings (e.g. lumber treatment) and water treatment (Ben-Sasson et al, 2016;Ma et al, 2016;Dankovich and Smith, 2014). The number of applications for regulatory approval of Cu-based nanopesticides has increased substantially in the past few years, highlighting the need for information about the likely exposure routes, doses and adverse effects on non-target organisms.…”
Section: Introductionmentioning
confidence: 99%
“…2-5 A novel and affordable technology for eliminating bacteria from contaminated water is a thick filter paper embedded with silver or copper nanoparticles. 2,6,7 …”
Section: Introductionmentioning
confidence: 99%
“…As an example, silverimpregnated ceramic filters effectively remove bacteria in the water but low water throughput and the release of silver ions into the treated water have been noted [4]. In another study, paper filters coated with copper nanoparticles have been shown to remove pathogens well but traces of copper were evident in the treated water [5]. Even though both of these point-of-use technologies are effective at microbial disinfection, they also require further water treatment to remove the residual chemicals in the water.…”
Section: Introductionmentioning
confidence: 99%